Factors Affecting Junior High School Teachers in Conducting Research: A Case Study - Ratih Yulianti (Language-Edu, 2020)
Teachers have important roles in the development of a nation. Teachers’ roles become broader nowadays since transferring the materials in the classroom is not the only duty to fulfill. Research is one of the government ways to improve and develop teachers’ professional development. There are factors affecting teachers’ in conducting research that need to be found out. This paper aims to find out the problems faced by teachers, factors affecting to conduct research and how the teachers solve the problems. The research method was sequential explanatory multi-method strategy with quantitative data that is explained in qualitative way. The research instruments were adapted questionnaire from Borg (2009) and the interview guide created by the researchers. There were 12 public and private junior high schools in Tulungagung that include 37 participants of English teachers chosen for this study. This research is expected to be helpful for the future researchers that have interest about teacher research and practically beneficial for the teachers in any level of school to be more engaged in doing the research besides teaching. Key words: factors, affecting, junior high school teachers, teacher research, Continuous Professional Development (CPD)